SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sampling microbial dynamics in the Salish Sea estuary: evaluating methods to capture cyanobacteria and cyanophage - Noelani R. Boise; Owen P. Leiser; Kristin Jones; Mahala Peter-Frank; Damon Leach; Stephen Crafton-Tempel; Peter Regier; Ruonan Wu; Conner Phillips; Margaret S. Cheung; Connah G. M. Johnson; Scott J. Edmundson; et al. (Frontiers in Marine Science, 2026)
Introduction Picocyanobacteria from the genera Prochlorococcus and Synechococcus thrive across the globe in aquatic environments, have relatively small genomes, and have growth dynamics regulated by both viral interactions and abiotic conditions, making them excellent model organisms for exploring host-pathogencoevolution. Methods We developed and refined methods to sample and sequence cyanobacteria, cyanophages, and measured features of their abiotic environment. Results The protocol described herein can successfully discriminate large-cell eukaryotic organisms, but size fractionation of picocyanobacteria appears to be affected by the presence of free DNA, multicellular structures, and abundant tycheposons. Our preferred final protocol from this exploratory effort included a combination of in-line and single vacuum flask filtrations, which reduced filtration processing time by over threefold in some cases compared to other tested methods, such as a fully in-line sequence or in-site filtrations. We successfully extracted an average of approximately 400–1200 ng for all filter fractions, with some variations between kits. Discussion The protocol described herein can successfully discriminate large-cell eukaryotic organisms, but size fractionation of picocyanobacteria appears to be affected by the presence of free DNA, multicellular structures, and abundant tycheposons.

Corrigendum to “Loss of c-Met signaling sensitizes hepatocytes to lipotoxicity and induces cholestatic liver damage by aggravating oxidative stress” [Toxicology 361–362 (2016) 39–48] - Luis E. Gomez-Quiroz; Daekwan Seo; Yun-Han Lee; Mitsuteru Kitade; Timo Gaiser; Matthew Gillen; Seung-Bum Lee; Ma Concepcion Gutierrez-Ruiz; Elizabeth A. Conner; Valentina M. Factor; Snorri S. Thorgeirsson; Jens U. Marquardt (Toxicology, 2026)

Biogeography and Anthropogenic Development Shape Mesopredator Distributions in a Rapidly Developing Region - Alex D. Potash; L. Mike Conner; Marcus Lashley; Michael Cherry; Andrew J. Edelman; Elina Garrison; Daniel U. Greene; William Gulsby; Matthew T. Hallett; David S. Jachowski; Paul Taillie; Robert A. McCleery (Journal of Biogeography, 2026)
Aim To investigate effects of anthropogenic development at regional and landscape scales on the distributions of mid‐trophic level mammalian predators (mesopredators) across the southeastern United States. Location The study area encompasses seven ecoregions across a large portion of the southeastern United States. Taxon Mammalian mesopredators. Methods We compiled trail camera data from 21 studies across the southeastern United States and used occupancy modelling to assess mesopredator distributions and account for heterogeneous detection probabilities. We examined drivers of occupancy at regional and landscape scales. At the regional scale, we assessed occupancy patterns across ecoregions differing in topography, productivity, and human population growth. At the landscape scale, we analysed the influence of land cover types (forest, developed, agriculture) and non‐native coyote ( Canis latrans ) activity on occupancy. Results Regionally, mesopredator occurrence was highest in ecoregions characterised by low productivity and greater topographic variability. Common species (predicted occupancy ≥ 0.19) showed positive associations with developed and agricultural land covers, while less common species (predicted occupancy ≤ 0.10) showed negative associations or were too rare to model. Coyote activity had mixed effects, positively associated with some species while negatively associated with others. Main Conclusions Anthropogenic development affects mesopredator communities at both regional and landscape scales, favouring generalist species that are tolerant of human‐modified landscapes.

Preliminary investigation of planar Sun-Ceres trajectories in variable restricted dynamical models - Robert A. Bettinger; Elliot A. Potter; Conner S. O’Malley; Annika J. Gilliam; Tyler J. Kapolka (Advances in Space Research, 2025)

Maximizing biological insights from instruments attached to animals - Roxanne S. Beltran; A. Marm Kilpatrick; Simona Picardi; Briana Abrahms; Gabriel M. Barrile; William K. Oestreich; Justine A. Smith; Max F. Czapanskiy; Arina B. Favilla; Ryan R. Reisinger; Jessica M. Kendall-Bar; Allison R. Payne; et al. (Trends in Ecology & Evolution, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Long‐term studies should provide structure for inclusive education and professional development - Max F. Czapanskiy; Lina M. Arcila Hernández; Cara Munro; Isabella Garfield; Adrien Bastidas; Allison R. Payne; Kelli Ong; Natalie A. Storm; Taiki Adachi; Conner M. Hale; Astarte Brown; Patrick W. Robinson; et al. (Ecology Letters, 2024)
Long‐term studies are critical for ecological understanding, but they are underutilized as inclusive opportunities for training ecologists. We use our perspective from the Año Nuevo elephant seal programme along with surveys from community members to propose that long‐term studies could be better leveraged to promote inclusive education and professional development in ecology. Drawing on our experiences as mentors and mentees, we demonstrate how long‐term studies can use their resources, including rich data , robust logistics and extensive professional networks , to improve recruitment and retention of diverse groups of trainees. However, practices such as unpaid labour and unclear expectations limit the utility of these resources for diversifying ecology. We discuss how we have structured our long‐term study to create more inclusive and equitable training opportunities. Acknowledging these transformations required substantial resources, we highlight funding sources and organizational partnerships that can promote investment in long‐term studies for broadening participation.

Correction: Presence of Hummock and Hollow Microtopography Reflects Shifting Balances of Shallow Subsidence and Root Zone Expansion Along Forested Wetland River Gradients - Ken W. Krauss; Gregory B. Noe; Jamie A. Duberstein; Nicole Cormier; Andrew S. From; Thomas R. Doody; William H. Conner; Donald R. Cahoon; Darren J. Johnson (Estuaries and Coasts, 2024)

Presence of Hummock and Hollow Microtopography Reflects Shifting Balances of Shallow Subsidence and Root Zone Expansion Along Forested Wetland River Gradients - Ken W. Krauss; Gregory B. Noe; Jamie A. Duberstein; Nicole Cormier; Andrew S. From; Thomas R. Doody; William H. Conner; Donald R. Cahoon; Darren J. Johnson (Estuaries and Coasts, 2024)

Effect of fast charging on degradation and safety characteristics of lithium-ion batteries with LiNi Co Mn Al1---O2 cathodes - Hanwei Zhou; Anuththara S. Alujjage; Maria Terese; Conner Fear; Tapesh Joshi; Vallabha Rao Rikka; Judith A. Jeevarajan; Partha P. Mukherjee (Chemical Engineering Journal, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Timing of seasonal events is correlated with social network position in a wild mammal - Conner S. Philson; Carla Bruebach; Taylor Bastian; Billy Barr; Daniel T. Blumstein (Behavioral Ecology and Sociobiology, 2024)
Across animal systems, abiotic environmental features, including timing of seasonal events and weather patterns, affect fitness. An individual’s degree of social integration also has fitness consequences, but we lack an understanding of how abiotic features relate to patterns of individual sociality. A deeper understanding of this relationship could be developed from studying systems where these two links with fitness have already been identified. We explored the relationship between individual social behavior and seasonal timing, seasonal length, and weather patterns. We used social network analysis on a sixteen-year dataset of a wild population of hibernating yellow-bellied marmots ( Marmota flaviventer ). We fit a series of generalized linear mixed models and found that longer growing seasons before winter hibernation and longer winters were associated with increased individual sociality in the following spring. However, later snowmelt was associated with decreased sociality that spring. We found no relationship between individual sociality and various measures of precipitation and temperature. This suggests that seasonal timing and length may be a more important driver of sociality than weather patterns in this system, both as a lag and contemporary effect. Seasonal timing and length may mediate the opportunity or intensity of social interactions. The entwined relationships between the seasonal schedule and weather, and the seemingly contradictory role of winter length and snowmelt, suggests the timing of seasons and its relationship with sociality is complex and further exploration of environment-sociality relationships is required across taxa. Significance statement While the adaptive benefits of social behavior are well studied, less is known about how features of the abiotic environment drive variation in individual social behavior. Given increasing stochasticity in the timing of seasonal events and weather patterns, mapping the environment-sociality relationship will provide important insights to the drivers of sociality in the wild. This is particularly salient for species most vulnerable to climate and environmental change, such as seasonal hibernators, like yellow-bellied marmots ( Marmota flaviventer ). We found that features of seasonal duration were positively associated with increased sociality, whereas the timing of seasonal onset was negatively associated. This work provides empirical evidence towards an important gap in the behavioral ecology literature.

Is flight initiation distance associated with longer-term survival in yellow-bellied marmots, Marmota flaviventer? - Daniel T. Blumstein; McKenna Sanchez; Conner S. Philson; Louis Bliard (Animal Behaviour, 2023)

145 4-H does more than show to grow: Rebuilding educational opportunities and emphasizing positive youth development in a previously show-only focused program - K. Irvine; C. Wickens; A. Schortinghouse; S. Conner (Journal of Equine Veterinary Science, 2023)

Comparison of methods (ROV, diver) used to estimate the composition and abundance of biota colonizing an offshore oil platform: A pilot study - Ann Scarborough Bull; Mary M. Nishimoto; Milton S. Love; Scott Clark; Katelin Seeto; Merit McCrea; Charin Park; Li Kui; Conner Jainese; Azivy Aziz; Jordan Angle (Continental Shelf Research, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Salinity, Water Level, and Forest Structure Contribute to Baldcypress (Taxodium distichum) Rhizosphere and Endosphere Community Structure - Candice Y. Lumibao; Elizabeth Kimbrough; Stephen Formel; Richard H. Day; Andrew S. From; William H. Conner; Ken W. Krauss; Sunshine A. Van Bael (Wetlands, 2020)

Abundance and phenology patterns of two pond-breeding salamanders determine species interactions in natural populations - Thomas L. Anderson; Daniel J. Hocking; Christopher A. Conner; Julia E. Earl; Elizabeth B. Harper; Michael S. Osbourn; William E. Peterman; Tracy A. G. Rittenhouse; Raymond D. Semlitsch (Oecologia, 2015)

Using extended pedigrees to identify novel autism spectrum disorder (ASD) candidate genes - Marc Woodbury-Smith; Andrew D. Paterson; Bhooma Thiruvahindrapduram; Anath C. Lionel; Christian R. Marshall; Daniele Merico; Bridget A. Fernandez; Eric Duku; James S. Sutcliffe; Irene O’Conner; Christina Chrysler; Ann Thompson; et al. (Human Genetics, 2015)

GSL2 over-expression confers resistance to Pectobacterium atrosepticum in potato - Sara Mohan; Sathiyamoorthy Meiyalaghan; Julie M. Latimer; Michelle L. Gatehouse; Katrina S. Monaghan; Bhanupratap R. Vanga; Andrew R. Pitman; E. Eirian Jones; Anthony J. Conner; Jeanne M. E. Jacobs (Theoretical and Applied Genetics, 2014)

Use of Partial Area under the Curve Metrics to Assess Bioequivalence of Methylphenidate Multiphasic Modified Release Formulations - Ethan M. Stier; Barbara M. Davit; Parthapratim Chandaroy; Mei-Ling Chen; Jeanne Fourie-Zirkelbach; Andre Jackson; Stephanie Kim; Robert Lionberger; Mehul Mehta; Ramana S. Uppoor; Yaning Wang; Lawrence Yu; et al. (The AAPS Journal, 2012)

Allele diversity for the apoplastic invertase inhibitor gene from potato - Sagar S. Datir; Julie M. Latimer; Susan J. Thomson; Hayley J. Ridgway; Anthony J. Conner; Jeanne M. E. Jacobs (Molecular Genetics and Genomics, 2012)

Erratum to: In Vitro Considerations to Support Bioequivalence of Locally Acting Drugs in Dry Powder Inhalers for Lung Diseases - S. L. Lee; W. P. Adams; B. V. Li; D. P. Conner; B. A. Chowdhury; L. X. Yu (The AAPS Journal, 2011)

Managing non‐target, data‐poor species using catch limits: lessons from the Alaskan groundfish fishery - R. F. REUTER; M. E. CONNERS; J. DICOSIMO; S. GAICHAS; O. ORMSETH; T. T. TENBRINK (Fisheries Management and Ecology, 2010)
The 2006 reauthorisation of the Magnuson‐Stevens Fishery Conservation and Management Act requires annual catch limits for all target and non‐target species within federally managed fisheries in the United States. In Alaska, both target and non‐target species in the Alaska groundfish fisheries have been managed using catch limits since the early 1990s. Non‐target species that are caught incidentally in a fishery require monitoring to ensure that the population is not negatively impacted by commercial fishing. Resource assessment scientists have been challenged with obtaining sufficient data to recommend an acceptable catch level for management of these species. This paper reviews three case studies where a catch limit is determined for non‐target species when certain data are limited: (1) varying levels of biomass and catch data for all species within a species group or complex; (2) adequate catch data but no biomass data; (3) emerging target fishery of data‐poor species, plus an example of how a complex of ecosystem component species is managed.

Water level observations in mangrove swamps during two hurricanes in Florida - Ken W. Krauss; Thomas W. Doyle; Terry J. Doyle; Christopher M. Swarzenski; Andrew S. From; Richard H. Day; William H. Conner (Wetlands, 2009)

Efficient isolation, culture and regeneration of Lotus corniculatus protoplasts - S. V. Raikar; R. H. Braun; C. Bryant; A. J. Conner; M. C. Christey (Plant Biotechnology Reports, 2008)

Whole genome amplification from plant cell colonies of somatic hybrids using strand displacement amplification - S. V. Raikar; C. Bryant; R. Braun; A. J. Conner; M. C. Christey (Plant Biotechnology Reports, 2007)

Transgenic Potato Lines Expressing cry1Ba1 or cry1Ca5 Genes are Resistant to Potato Tuber Moth - S. Meiyalaghan; J. M. E. Jacobs; R. C. Butler; S. D. Wratten; A. J. Conner (Potato Research, 2007)

Intragenic vectors for gene transfer without foreign DNA - Anthony J. Conner; Philippa J. Barrell; Samantha J. Baldwin; Annemarie S. Lokerse; Pauline A. Cooper; Astrid K. Erasmuson; Jan-Peter Nap; Jeanne M. E. Jacobs (Euphytica, 2007)

Assessment of yield loss caused by mycosphaerella blight in field pea crops in western Canada - H. Su; S. F. Hwang; K. F. Chang; R. L. Conner; A. G. Xue; T. D. Warkentin; S. F. Blade; G. D. Turnbull (Journal of Plant Diseases and Protection, 2006)

Variations in virulence and genome of Mycosphaerella pinodes isolates from field peas in central Alberta, Canada - H. Su; S. F. Hwang; K. F. Chang; R. L. Conner; R. J. Howard; G. D. Turnbull (Journal of Plant Diseases and Protection, 2006)

Geographic patterns in the demersal ichthyofauna of the Aleutian Islands - E. A. LOGERWELL; K. AYDIN; S. BARBEAUX; E. BROWN; M. E. CONNERS; S. LOWE; J. W. ORR; I. ORTIZ; R. REUTER; P. SPENCER (Fisheries Oceanography, 2005)
The goals of this research were to investigate geographic patterns in the Aleutian Island region's demersal ichthyofauna and to determine whether they reflected the physical and biological oceanographic patterns documented by other authors in this volume. The analyses were structured according to the level of organization: at the community level, patterns in species occurrence and community structure were investigated; at the population level, distribution and abundance were examined; at the individual level, food habits and growth were studied. There were step‐changes in species occurrence, diversity, population distribution and food habits at Samalga Pass and at sites farther west. These longitudinal trends indicated physical and biological variation along the length of the Aleutian Islands chain; however, depth‐related patterns were as common as longitudinal patterns in demersal fish distribution. In addition, high catches of patchily distributed species occurred in areas expected to be biological ‘hot spots’ because of increased productivity and prey availability. These patterns suggest linkages between demersal fish ecology and the biophysical processes described by other authors in this volume and indicate that inter‐disciplinary research is needed to elucidate the underlying mechanisms.

Microbial communities of Solanum tuberosum and magainin-producing transgenic lines - M. O’Callaghan; E. M. Gerard; N. W. Waipara; S. D. Young; T. R. Glare; P. J. Barrell; A. J. Conner (Plant and Soil, 2005)

Differences in the growth stages of Erysiphe pisi on cultivars of field pea (Pisum sativum L.) - H. Su; S. F. Hwang; K. F. Chang; R. L. Conner; R. J. Howard; G. D. Turbull; S. F. Blade (Journal of Plant Diseases and Protection, 2004)

The Herpes Simplex Virus (HSV) Protein ICP34.5 is a Virion Component that Forms a DNA-Binding Complex with Proliferating Cell Nuclear Antigen and HSV Replication Proteins - June Harland; Paul Dunn; Euan Cameron; Joe Conner; S Moira Brown (Journal of NeuroVirology, 2003)

Biopharmaceutics Classification System: The Scientific Basis for Biowaiver Extensions - Lawrence X. Yu; Gordon L. Amidon; James E. Polli; Hong Zhao; Mehul U. Mehta; Dale P. Conner; Vinod P. Shah; Lawrence J. Lesko; Mei-Ling Chen; Vincent H. L. Lee; Ajaz S. Hussain (Pharmaceutical Research, 2002)

Characterisation of Triticum vavilovii-derived stripe rust resistance using genetic, cytogenetic and molecular analyses and its marker-assisted selection - H. S. Bariana; G. N. Brown; N. U. Ahmed; S. Khatkar; R. L. Conner; C. R. Wellings; S. Haley; P. J. Sharp; A. Laroche (Theoretical and Applied Genetics, 2002)

Molecular-marker analysis of quantitative traits for growth and development in juvenile apple trees - P. J. Conner; S. K. Brown; N. F. Weeden (Theoretical and Applied Genetics, 1998)

Molecular cytogenetic characterization of Thinopyrum intermedium-derived wheat germplasm specifying resistance to wheat streak mosaic virus - Q. Chen; B. Friebe; R. L. Conner; A. Laroche; J. B. Thomas; B. S. Gill (Theoretical and Applied Genetics, 1998)

New Criteria for the Identification of Animal Fats Preserved in Archaeological Pottery - R. P. Evershed; H. R. Mottram; S. N. Dudd; S. Charters; A. W. Stott; G. J. Lawrence; A. M. Gibson; A. Conner; P. W. Blinkhorn; V. Reeves (The Science of Nature, 1997)